Rethinking the Legitimacy of Global Governance: On the Need for Sociological Research and Philosophical Foundations - Dirk Peters (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2013)
What would constitute a legitimate global order? Dirk Peters argues that current research on this issue is one-sided: it takes Western democracy as a universal standard and focuses discussion on how aspects of democracy can be applied at the global level. But instead of promoting a universal standard, says Peters, research needs to listen to the actors involved in global governance. There can be no legitimate global order without taking into account what these actors regard as legitimate, and this will not necessarily be a model based on Western democracy. This point of view is endorsed by Frank Gadinger, who proposes a methodological technique from sociology to facilitate empirical research in this area. By reconstructing the arguments that 'ordinary actors' employ in the global political arena, we can reveal what they consider legitimate. Daniel Gaus, by contrast, takes issue with Peters's critique of democracy as a universal standard. Peters may well be correct in contending that Western democratic institutions are not suitable as a basis for legitimizing global politics, says Gaus, but the very act of listening to the governed, and making their conceptions of legitimacy the yardstick of legitimate governance, is itself a democratic endeavour.
urn:nbn:de:hbz:464-20150105-091129-3
Keywords: 320; Crises of legitimacy; global governance; research methodology; philosophy; normative concepts; pragmatic sociology